Participation and the mystery : transpersonal essays in psychology, education, and religion - Ferrer, Jorge N. (Jorge Noguera), 1968- (State University of New York Press, 2017)
Participation and the Mystery is both an introduction to and expansion of Jorge N. Ferrer's groundbreaking work on participatory spirituality, which holds that human beings are active cocreators of spiritual phenomena, worlds, and even ultimates. After examining the impact of his work since the publication of Revisioning Transpersonal Theory, Ferrer discusses the relationship between science and transpersonal psychology, the nature of a fully embodied spirituality, and the features of integral spiritual practice. The book also introduces a participatory philosophy of education and applies it to the academic teaching of mysticism and a novel approach to embodied spiritual inquiry. Critically engaging the influential work of Stanislav Grof, Ken Wilber, and A. H. Almaas, Ferrer concludes with an original solution to the problem of religious pluralism that affirms the ontological richness of religious worlds while avoiding the extremes of perennialism and contextualism, offering a hopeful vision for the future of world religion. Participation and the Mystery is an invaluable resource to anyone seeking to deepen their understanding of participatory approaches to transpersonal psychology, integral and contemplative education, contemporary spirituality, and religious studies. Book jacket.